Factors Influencing Employee Turnover in the Hotel Industry in Chitwan - Giri, Sushmita; Dhungana, Govinda Prasad (BMC Journal of Scientific Research, 2024)
Employee turnover is a critical issue in the hotel industry, posing significant financial and operational challenges, particularly due to the sector's higher turnover rates compared to other industries. This study aims to identify key factors influencing turnover intentions, such as working environment, career growth opportunities, compensation, and job satisfaction. A quantitative research design was employed to identify the factors influencing employee turnover. The study population consisted of staff from tourist-standard hotels registered with the Regional Hotel Association of Nepal (RHAN). Twelve hotels were selected by convenience sampling, and 180 questionnaires were distributed, with 100 completed responses, resulting in a 55.5% response rate. The findings revealed that job satisfaction had a significant negative impact on turnover intentions, while other factors like working environment, career growth, and compensation were not statistically significant predictors. The study concludes that improving job satisfaction is essential to reducing turnover. The implication of this study is that managers or owners should prioritize initiatives to enhance job satisfaction as a strategic approach to reducing employee turnover intentions.